Perancangan Sistem Penjadwalan Mesin Hybrid Flow Shop dengan Algoritma Levyflight Discrete Firefly - Andrew Verrayo Limas; J. Sudirwan; Siti Nur Fadlilah (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The main issues that have been encountered in PT Surya Toto Indonesia is companies do not know how to measure the performance of the production process so as the utilization of resources that will be used isn’t yet to be known with efficiently. The purpose of this case studies is creating a better production processes by proposing a better and systematic scheduling information system. An Object Oriented Analysis and Design method is used to determine system’s requirements and design of the system architecture. Metaheuristic methods such as Discrete algorithms Levy-flight Firefly is used to improve the performance of the Hybrid Flow Shop machine scheduling become more better. Indicators that are used to determine the performance of the scheduling is makespan and lateness. Results from this algorithm is makespan value of 305.27 hours with lateness value of 10.92 which determine that there is no delays in scheduling. Scheduling information system was designed three primary capabilities, which are integrated data management, inventory management and a systematic and accurate scheduling system.